نظرية نمو اللغة وفرضية أسباب انتشارها من خلال الدوغمائية التاريخية والفلسفة المنطقية - Fina Aunul Kafi (INAIFAS PRESS, 2020)
The growth of language and how it spreads is still an unsolved puzzle. Even some scholars appreciate the objectivity of solving this problem due to the lack of data and tend to be speculative. Religious and scientific circles have their own beliefs in the idea of ​​language growth and dissemination. Moreover, theories of language growth have their own foundations of truth. This study aims to remap how language grows and spreads along with human development. Researchers used a qualitative descriptive method by extracting data through the literature. The results of this study are that there are two major theories that dominate this problem field, namely the theory which states that language is a gift from God and another theory states that language is the result of human creation. The researcher concludes that the number of existing theories related to this problem will taper into these two camps.